Determination of the impact of variation in wheat (triticum aestivum l.) flour quality on the consumer acceptability of frozen dough products - van der Walt, Marieta Johanna (Bloemfontein: Central University of Technology, Free State, 1998)
Following the deregulation of the wheat industry, a considerable diversification was observed in the retail of wheat dough products. The processing of frozen dough products, appears to be particularly promising as the convenient nature of the products complements the requirements of the small scale entrepreneur. The quality specifications of flour destined for frozen dough products appear not to have been specified in South Africa. Moreover, infonmation on the effect of South African cultivars on the processing of frozen dough, as well as the consumer acceptance of such products, are virtually non-existent. The primary objective of this study was to determine the impact of variation in flour quality on the sensory and thus marketing properties of a range of frozen products. The second objective was to identify criteria, or possibly a protocol, according to which flour types suited to the production of frozen dough products could be selected. The third objective was to identify the reological characteristics of flours suited to the production of frozen dough products. Flour and dough quality were assessed by means of standardised rheological techniques to determine the rheological properties of five different wheat cultivars and a commercial flour. The flour sources used were derived from the commercial hard red wheat cultivars (Triticum aestivum L.) Molen, Gamtoos, Palmiet, Betta and Tugela. Four frozen dough products were produced and assessed by a consumer panel to indicate the impact of flour source. These products were Hamburger Buns, Fruit Buns, Wholewheat Buns and Standard Brown Loaves. Flour from the cultivars, Tugela and Betta with their inherent strong dough quality features, were identified as being the most suitable for the production of frozen dough products. The introduction of AMMI, a multivariate statistical technique, in analysing the interaction between product and cultivar, diversified this study. According to AMMI-rankings, the visual texture of bran-containing products was identified as the most valuable sensory characteristic in predicting consumer acceptability. Canonical correlation analysis indicated that Mixograph Midline and Alveograph assessments could serve as valuable predictors in assessing the suitability of flour types for the production of frozen dough products.
Thesis
Keywords: Dough; Frozen foods; Batters (food)